Increase survival of droughted mangosteen plants by hydrogel polymer incorporation - Izhar, Adiwirman (2001)
Hydrogel polymer treatments within the root environment increase mangosteen plant ability to withstand plant water stress. The application of hydrogel polymer could not increase plant photosynthetic and stomatal conductance capability. Increasing concentration of hydrogel incorporation per tree did not improve stomatal conductance and photosynthesis rate under water stress condition.